The Correlation of Watching “Anak Jalanan” Drama Series and Perceived Reality with Children’s Violent Behavior - Miranti Januarizky; Dra. Sri Widowati Herieningsih, MS (Interaksi Online, 2017)
Lots of violent cases which been done by kids towards other kids because they are imitating those violent scenes from television. One of those television programs that contains quite amount of violent is “Anak Jalanan”. The high intensity of watching television enable them to imitate those violent scenes instantly. Besides, children could not entirely differ reality, so they will perceive those scenes as reality which is happens in our daily life. This research’s objective is to reveal the correlation between watching “Anak Jalanan” drama series on television and perceived reality with children’s violent behavior. Social learning and perceived reality theories are used to support the research. This is an explanatory kind of research, using 100 children (age 7-12) in Semarang as research sample which are collected using non probability sampling technique. While data analysis has been done using Kendall Tau-b correlation test. Hypotheses test results show there is a relation between watching “Anak Jalanan” drama series on television with children’s violent behavior, with significancy number as much as 0,033 and correlation coefficient as much as 0,151. Those results showing a weak relation with positive relation. As of, if the intensity of watching “Anak Jalanan” drama series is high, then the violent behavior will be high as well. Otherwise, if if the intensity of watching “Anak Jalanan” drama series is low, then the violent behavior will be low as well. Furthermore, hypotheses test result showing significancy number of “perceived reality” variable is as much as 0,104 and correlation coefficient number is as much as -0,114. Those mean, there is no significant relation between perceived reality with children’s violent behavior. Parents are suggested to make efforts in restricting children’s tv watching consumptions and practicing an active mediation kind of supervision, so that parents should have media consumption effect awareness in order to minimized negative effect caused by television, especially violent behavior effect.